2019
DOI: 10.1163/15685403-00003884
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of exotic invasive species of the brine shrimp Artemia Leach, 1819 (Branchiopoda, Anostraca) in Al Wathba Wetland Reserve (U.A.E.; Abu Dhabi)

Abstract: The taxonomic identity of an unknown Artemia population inhabiting the Al Wathba Wetland Reserve in Abu Dhabi, U.A.E., was determined using phylogenetic analysis of the mitochondrial marker Cytochrome Oxidase Subunit 1 (COI). The results showed that the examined population belongs to an exotic invasive species, Artemia franciscana. Based on the distribution pattern of haplotypes, the studied population could possibly have originated from that inhabiting the Great Salt Lake (Utah, U.S.A.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The occurrence of Artemia in UAE had been recorded in two geographical sites including in Al Wathba Wetland Reserve 22 and Godolphin Lakes 23 . A molecular phylogenetic study has confirmed that population in Al Wathba Wetland Reserve belonged to an exotic American A. franciscana 20 . Our results have also documented the colonization of same species in Godolphin Lakes locality.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The occurrence of Artemia in UAE had been recorded in two geographical sites including in Al Wathba Wetland Reserve 22 and Godolphin Lakes 23 . A molecular phylogenetic study has confirmed that population in Al Wathba Wetland Reserve belonged to an exotic American A. franciscana 20 . Our results have also documented the colonization of same species in Godolphin Lakes locality.…”
Section: Discussionmentioning
confidence: 77%
“…The San Francisco Bay (SFB) and Great Salt Lake (GSL) are the two main sources of Artemia that have usually been used to culture in other saline ecosystems for industrial aquaculture and fishery activates to produce Artemia cysts and biomass 13,20,21,34 , for this reason these populations were considered in this analysis to find out the genetic alterations of the colonized populations in new non-native environments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations